KAJIAN KETERSEDIAAN AIR PADA DAERAH TANGKAPAN AIR (DTA) WADUK PAMUKKULU - Hendy Adiyat Nugraha; Dyah Ari Wulandari (LPPM Universitas Abdurrab, 2025)
The Pamukkulu Dam is a multi-purpose dam designed to serve the irrigation water needs of the Pamukkulu Irrigation Area (D.I Pamukkulu), provide raw water supply, and control flooding. The dam has a total storage capacity of 82,57 million m3, with a dead storage volume of 4,95 million m3. Currently, the dam is in the preparation stage for reservoir operation, where water availability is a critical factor. Water availability is calculated based on the inflow discharge pattern for each condition year using the Weibull method. The inflow (water availability) is determined by transforming rainfall data into streamflow discharge using the F.J. Mock method. The inflow discharge of the reservoir is categorized into three conditions: